Correlation of Farmers Characteristics to Motivation in Sheep Farming at Ngudi Makmur II and Tirto Kencono Farmers Groups Banyudono Village Dukun District - Haris Tri Wibowo; Joko Daryatmo (Jurnal Penyuluhan Pertanian, 2023)
Motivation is one aspect that determines the success of livestock business as an economic activity in increasing income and fulfilled family needs. The research was carried out in Ngudi Makmur II Farmers Group and Tirto Kencono Farmers Group, Banyudono Village, Dukun District from 05 March to 30 April 2018. The aim were to know the level of motivation of farmers in the cultivation of sheep and determine the relation between characteristics of the farmers to motivation in sheep farming. The study design used was descriptive quantitative. The variables of this research consisted of independent variables such as the characteristics of farmers (age, education level, farming experience, the number of livestock ownership and the number of family dependents) and the dependent variable in the form of farmers motivation. Respondents in this study were 35 people taken by census method. Data were collected by observation and interview. Motivation levels were analyzed descriptively while the relationship between variables were analyzed by Rank Spearman correlation. The results showed that 2.86% of farmers at moderate level, 42.86% of farmers at high level and 54.29% of farmers at very high level. The aging of farmers is likely to decrease the motivation in the cultivation of sheep, the higher the level of education of farmers that motivation increases, the more the number of livestock owned by the motivation tends to increase, farmers with more experience tend to have a higher motivation and the greater number of dependents the motivation of farmers tend more increasing.